MODEL PEMBELAJARAN TERPADU (STUDI KASUS DI YAYASAN MUHAMMAD YA'QUB JOMBANG) - Siti Hesniyatul Jamila (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2020)
This study aims to describe the implementation of integrated learning models in educational institusions that are under the auspices of the foundation of Muhammad Ya’qub Jombang. Which include visits from the factors of purpose, educatos, students, learning strategies, materials, infrastructure and evaluation of integrated learning in educational institusions which is under the auspices of the foundation of Muhammad Ya’qub Jombang. The implementation of an integrated learning models on Biology subjects is called the shared models (divided model). However, the integrated learning models in educational institusions under the auspices of the foundation of Muhammad Ya’qub Jombang is superior because there is also educational training in learning. The purpose of this learning is the realization of the vision mission that has been integrated with the objectives of national education and the value of education contained in QS. Al-Baqarah verses 39 and 132. Judging from the factors of educators, there are feel still differences in quality in collaborating and integrating learning. Judging from the factors of student, they have understood the importance of learning. Viewed from the infrastructure facilities, namely the national examination secondary book and Biology pocket book, the Harun Yahya DVD learning media and the 2 in 1 Science (SD/MI) book. Judging from the factors of strategy factor of collaboration and integration, the intended collaboration is by practice the value of education contained in QS. Al-‘Alaq : 1 and integrate with religious values integrated with the discussion. Judging from the material factors, divided into to major groups, namely divinity and humanity. Judging from the evaluation/ assessment system factors: success in learning is seen in the success of the cognitive, affective, and psychomotor domains, as well as substandard enrichment for special and remedial students for students. Suggestion: Implementation of integrated learning model in educational institusions under the auspices of the foundation of Muhammad Ya’ub Jombang for a while has a lot of positive values. Therefore, it is better to be refined and taken in consideration to be implemented through policy nationally.